(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2023)
In this paper, we present a method for measuring the one-way speed of light. In order to achieve this, it is necessary to solve two problems. The rst problem is how to synchronize the clocks at the source and the detector, and the second problem is to prove that the slow movement of one of the clocks does not significantly a ect the already established synchronization between the two clocks.